Co-accumulation of microbial residues and particulate organic matter in the surface layer of a no-till Oxisol under different crops - Martins, Marcio R. [UNESP]; Angers, Denis A.; Cora, Jose E. [UNESP] (Pergamon-Elsevier B.V. Ltd, 2012)
In the absence of significant mechanical disturbance such as under permanent no-till (NT), crop type should be a prominent factor controlling soil organic C (SOC) pools. Microbial cell residues have been shown to be influenced by plant species and are believed to contribute significantly to soil organic matter formation. We performed a study to investigate the co-accumulation of microbial cell wall residues (glucosamine, GlcN and muramic acid, MurN) and organic C (total and particle-size fractions) in the surface layer (0- to 5-cm depth) of an Oxisol after 7 yr under NT, as affected by different crop types. SOC content associated with pigeon pea [Cajanus cajan (L) Millsp.] was 20% and 18% higher than that with corn (Zea mays L) or sunflower (Helianthus annuus L.), respectively. The highest particulate organic C (POC) content in soil was also found under pigeon pea, which showed values 54, 46, and 48% higher than under corn, sunflower, and oilseed radish (Raphanus sativus L var. oleiformis Pers.), respectively. Changes in POC explained most of the variation in SOC. The positive impact of pigeon pea on POC and SOC was attributed to rapid decomposition of its residues, due to their low C/N ratio, followed by selective preservation of lignin-rich particulate organic matter. The accrual of POC was closely associated with the accumulation of fungal and bacterial cell wall residues. This may be due to preferential feeding of fungi and bacteria on recently deposited plant-derived C sources present in the form of particulate organic matter. This observation is consistent with a recent model suggesting that microbial residues play a greater role in the formation of SOC than previously considered. We emphasize that this effect was mediated by the accumulation of POC and influenced by crop type. Crown Copyright (C) 2012 Published by Elsevier Ltd. All rights reserved.
Keywords: Amino sugars; Crop rotation; Microbial residues; No-till; Oxisol; Particulate organic matter; Plant type; Winter crop